Blade Runner 2049 and the 'quality' Hollywood film. (February 2020) - King, Geoff
Abstract : This article provides an analysis of how Blade Runner 2049 (Villeneuve US/UK/Canada/Hungary/Spain 2017) can be understood to occupy the position of a 'quality' Hollywood film through two main points of focus. First, the essay examines the textual basis on which the film can be seen to claim, and was accorded, a particular kind of 'quality' status, including examination of a number of bases on which notions of quality of this variety are articulated within prevailing hierarchies of cultural value. This includes what can be seen as 'serious' and 'substantial' thematic dimensions and aspects of style ranging from narrative structure and pacing to general audiovisual qualities and use or otherwise of elements such as action and the spectacular. Second, it considers what space is available in the contemporary corporate studio system for the production of works that depart from dominant norms to some degree in such ways. Rather than being taken as evidence of some kind of breakthrough or as an entirely one-off anomaly, Blade Runner 2049 is examined as evidence of an ongoing availability of a certain margin for the production of films that can accorded 'quality' status of this kind within Hollywood.